OC-141 Upper GI bleeding in Scotland 2000–2010: improving outcome but a significant weekend effect. (28th May 2012) - Ahmed, A; Armstrong, M; Robertson, I; Blatchford, O; Morris, J; Stanley, A
Abstract : Introduction: Recent studies have suggested a reduction in incidence of upper GI haemorrhage (UGIH) and a possible worse outcome if patients present at weekends. Our aim was to assess trends in numbers and mortality of patients admitted with UGIH in Scotland and to examine whether weekend presentation affected outcome. Methods: We identified 23 ICD-10 codes that identified UGIH and interrogated ISD Scotland data using these codes for the 10-year period 2000–2010. We analysed the annual numbers of patients and their 30-day mortality during this period, comparing length of stay and mortality for those admitted at weekends and weekdays. Results: A total of 61 574 Scottish residents were admitted to Scottish hospitals with a diagnosis of UGIH during the years 2000/1–2009/10. There was no significant change in annual numbers of admissions during this period, but there was a reduction in 30-day mortality from 10.3% to 8.8% (p<0.001). For the whole study period, patients admitted with UGIH at weekends had a higher 30-day mortality compared with those admitted on weekdays (p<0.05). A significantly higher mortality for patients admitted at weekends was seen in 9 of the 10 years, including each of the last five years. This was despite patients admitted at weekends being younger than those admitted on weekdays (57.6 yrs vs 58.8 yrs; p<0.001). Over the study period there was a greater length of stay for patients admitted on weekends compared with weekdays (p<0.05), with the greatest difference found in the most recent year of study. Conclusion: There has been a gradual reduction in mortality for patients admitted with UGIH in Scotland over the past 10 years. Despite a younger age, patients admitted at weekends had consistently higher mortality and greater length of stay compared with weekday admissions. Competing interests: None declared. References: 1. Button, et al. Aliment Pharmacol &Ther 2011;33 :64–76. 2. Dorn, et al. Dig Dis Sci 2010;55 :1658–66.